The human right of HIV positive persons to non-discrimination in getting life insurance in South Africa - Nienaber, A.G. (Annelize Gertruida) (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2003.